EFEKTIFITAS LITERASI MELALUI GAME NABUNG SAHAM GO TERHADAP KEPUTUSAN MEMBELI SAHAM SYARIAH (Equilibrium: Jurnal Ekonomi Syariah, 2019)
This  research aims to determine  an influence of understanding of students of IAIN Kudus through the game of saving stock go to the decision to buy Islamic shares. The research approach uses a quantitative approach with the path analysis method through the warpPLS 6.0 application. Literacy as an independent variable is a buying decision as an dependent variable and game media as an intervening variable. The subjects in this study were 100 students of IAIN Kudus using purposive random sampling technique. The results showed that there is an influence of literacy through games on purchasing decisions with a significance of 0.003. The indirect effect is 0.192 and the total effect is 0.569. This means that literacy through the savings game go stock has a positive and significant effect on the decision to buy Islamic stocks.